2020
DOI: 10.1080/00206814.2020.1821250
|View full text |Cite
|
Sign up to set email alerts
|

Petrogenesis of the peralkaline Dutsen Wai and Ropp complexes in the Nigerian younger granites: implications for crucial metal enrichments

Abstract: Supplementary document for the paper: Petrogenesis of the peralkaline Dutsen Wai and Ropp complexes in the Nigerian Younger Granites: Implications for crucial metal enrichments. Amuda et al., 2020. Local geology and sampling Dutsen Wai plutonsThe complex consists of alkaline epizonal plutons, discordantly intruded into migmatite and granite gneiss basement. It comprises of two main phases; volcanic and plutonic rock units peculiar to the NYG province. Most of the intrusive plutons (over 90%) are made up of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 113 publications
(9 reference statements)
4
19
0
Order By: Relevance
“…As is typical of southern ring complexes in the Nigerian alkaline anorogenic province, the Ropp complex consists of abundant biotite granites (Figure 1c), which, together with the minor albite arfvedsonite granites occasionally host rare metal Nb–Sn mineralization (Amuda et al, 2020; Buchannan et al, 1971). In particular, the biotite granite in central part of the Ropp complex (in Bukka Bakwai village) host the largest primary columbite with economic values up to 1 lb per ton, while in terms of tin production, the Ropp biotite granites are the second largest, after the Jos‐Bukuru biotite granites (Buchannan et al, 1971; Jacobson et al, 1958).…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…As is typical of southern ring complexes in the Nigerian alkaline anorogenic province, the Ropp complex consists of abundant biotite granites (Figure 1c), which, together with the minor albite arfvedsonite granites occasionally host rare metal Nb–Sn mineralization (Amuda et al, 2020; Buchannan et al, 1971). In particular, the biotite granite in central part of the Ropp complex (in Bukka Bakwai village) host the largest primary columbite with economic values up to 1 lb per ton, while in terms of tin production, the Ropp biotite granites are the second largest, after the Jos‐Bukuru biotite granites (Buchannan et al, 1971; Jacobson et al, 1958).…”
Section: Introductionmentioning
confidence: 97%
“…These features are requisite attributes that can provide crucial information on the petrogenesis and tectonic implications of anorogenic alkaline magmatism, a hotly debated topic in the geologic literature. Indeed, recent studies have shown that the Nigerian ferroan granites were generated as a result of fractional crystallization of highly differentiated basaltic (OIB) magmas from the enriched lithospheric mantle with variable contributions from the lower crust (Ahmed et al, 2021; Amuda et al, 2020; Girei et al, 2019; Kamaunji et al, 2020). However, other workers (Girei et al, 2020; Vincent et al, 2021) opined that the Nigerian A‐type granites, particularly the highly oxidized and less radiogenic Mo– and Pb–Zn mineralized biotite granites from Mada and Ningi‐Burra complexes, were derived from the lower crust with upper mantle involvement.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations